The Sociological Approaches of Exploring Social Protection system - Yarmaloyan, Marine (Journal of Sociology: Bulletin of Yerevan University, 2018)
A social protection system that ensures the safe existence of a population, preventing social risks and their consequences, is an essential link in the institutional social mechanism in the most developed country in the world. The article is devoted to the sociological analysis of the system of social protection. The author substantiates the use of systemic and structural-functional approaches for a comprehensive sociological analysis of the social protection system.